Pengaruh Latihan Menggunakan Karet Ban Sepeda Terhadap Penguasaan Teknik Dasar Panahan Pada Atlet Panahan Tingkat Pemula - Juniarni Hardi, Veny (STKIP Pasundan, 2022)
This study aims to determine the effect of training using rubber bicycle tires in mastering basic archery techniques for beginner level archery athletes. This research is an experimental research using pre-experimental methods with data collection techniques using treatment, pretest and posttest as research instruments. The population of this study were archery UKM STKIP Pasundan athletes with a total of 10 athletes, the sample used was 10 athletes using the sampling method, namely the total sampling technique. Data analysis used the IBM SPSS Statistics 25 application. Data analysis started by calculating the mean/average value of the results of the archery test conducted on the sample (Archery UKM STKIP Pasundan students, the result was that the average value of P1 (Assessor 1) was 17.3 of 7, 8 (pretest) is smaller than P2 (assessor 2) with an average value of 17.8 out of 8.7 (pretest).